Early miR-223 Upregulation in Gastroesophageal Carcinogenesis. Issue 3 (26th February 2017) - Fassan, Matteo; Saraggi, Deborah; Balsamo, Laura; Realdon, Stefano; Scarpa, Marco; Castoro, Carlo; Coati, Irene; Salmaso, Roberta; Farinati, Fabio; Guzzardo, Vincenza; Arcidiacono, Diletta; Munari, Giada; et al.
Abstract: Objectives: To test miR-223 upregulation during gastric (intestinal-type) and Barrett esophageal carcinogenesis. Methods: miR-223 expression was assessed by quantitative reverse transcription polymerase chain reaction in a series of 280 gastroesophageal biopsy samples representative of the whole spectrum of phenotypic changes involved in both carcinogenetic cascades. The results were further validated by in situ hybridization on multiple tissue specimens obtained from six surgically treated gastroesophageal adenocarcinomas. miR-223 expression was also assessed in plasma samples from 30 patients with early stage (ie, stages I and II) gastroesophageal adenocarcinoma and relative controls. Results: In both gastric and esophageal models, miR-223 expression significantly increased along with the severity of the considered lesions (analysis of variance, P < .001). Among atrophic gastritis and long-segment Barrett esophagus samples, miR-223 overexpression was significantly associated with the score of intestinal metaplasia. miR-223 plasma levels were significantly upregulated in patients with cancer compared with controls ( t test, both P < .001). Conclusions: miR-223 early upregulation observed in tissue samples and its diagnostic value in discriminating patients with early adenocarcinoma by plasma testing provide a solid rationale for further exploring the diagnostic reliability of this microRNA as a novel biomarker in gastroesophageal adenocarcinoma secondary prevention strategies.